THE EFFECT OF GENDER INEQUALITY ON INCOME PER CAPITA: PANEL DATA ANALYSIS FROM 34 PROVINCES IN INDONESIA - Alamanda Alamanda (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2021)
The issue of gender inequality has become one of the 17 global UN Sustainable Development Goals. Gender equality is so important since it has been argued as one of the crucial determinants of economic growth and development. Although there have been numerous studies to investigate the correlation between gender inequality and income per capita, the empirical regarding this issue in the case of Indonesia is still minimum. Therefore, this paper tries to contribute to the discussion by analysing a panel data set of 34 provinces from 2015 to 2018 to examine the effect of gender inequality on income per capita in Indonesia. Using the Pooled OLS, Fixed Effect, and Random Effect Model, this paper finds that gender inequality has a negative significant impact on income per capita, which means the less the gap between men and women, the more income per capita. The empirical evidence suggests that a one-point decrease in Gender Inequality Index (GII) will increase income per capita by 0.65 to 0.71 percent on average. In other words, if the gap between men and women is eliminated in Indonesia (the GII equals zero), income per capita would increase by approximately 28.34 percent. Moreover, the paper finds that gender inequality has the same impact on income per capita across all regions in Indonesia.